Factors Relating to Food Safety Practices Among Indonesian Adolescents: A Descriptive Literature Review - Nawawi, Muhammad; Angriani, Yayu; Suyitno, Suyitno (Griya Eka Sejahtera, 2025)
Background: Food safety is a major public health concern, especially for adolescents who are experiencing significant physical and physiological changes. Ensuring proper food handling, storage, and preparation is crucial to prevent foodborne disease, which can have serious impacts on the health and development of young individuals. This review aimed to identify key Socio-demographic determinants that impact how Indonesian adolescent’s food safety practice.Methods: The literature review involved a comprehensive search of academic databases such as PubMed, Google Scholar, and JSTOR using keywords factors relating to food safety practice among Indonesian adolescents. Selected studies (13 articles) were evaluated using Data extraction was conducted using the Joanna Briggs Institute (JBI) form to identify key factors related, and the results were synthesized to uncover common themes and patterns affecting food safety practice.Results: The findings emphasize the interplay of socioeconomic status, education, and environment on food safety practice among adolescents.Conclusion: This study shows that it is very important to implement targeted interventions that encourage safer food handling behaviors, thus the need for targeted interventions to promote safer food handling behaviors. Strengthening food that requires integrating education system, enforcing stricter regulations, increasing safe food access, and using AI technology for awareness.